Merkelova bunka: morfologie, vývojový původ, funkce - Halata, Z; Grim, M; Baumann, K I (Casopis lekaru ceskych, 2003)
Merkel nerve endings are mechanoreceptors in the vertebrate skin. They were named after the person who first described them--F.S. Merkel (1875). They consist of large, pale cells with lobulated nuclei forming synapse-like contacts with enlarged terminal endings of myelinated nerve fibres. Inside the cell are intermediate filaments formed of simple cytokeratins and osmophilic granules containing variety of neuropeptides. In mammals, they can be found in the basal layer of the skin and in those parts of the mucosa, which is derived from ectoderm. In contrast, in birds these cells are located in the dermis. The largest accumulation of Merkel nerve endings was found in whiskers of most mammals apart from man. There has been a controversy concerning the origin of Merkel cells. Results from chick/quail chimeras and most recently also from double transgenic mice have shown that Merkel cells are derived from the neural crest. Merkel cell play a role in the mechano-transduction process. In response to mechanical stimuli calcium ions enter Merkel cell and trigger the release of neurotransmitter probably glutamate. Thus, Merkel cell appears to be essential for characteristic slowly adapting response of these receptors during maintained mechanical stimuli. Cells in the skin of a similar appearance as Merkel cells are probably part of the diffuse neuroendocrine system and they do not function as mechanoreceptors. These cells, rather than those in mechanoreceptors, are most likely the origin of the highly malignant skin cancer called Merkel cell carcinoma.
Keywords: Animals; lidé; Merkelovy buňky; zvířata; Merkel Cells; Humans